Идет бычок, качается - Барто Агния Львовна (Любимые книги детства, 2008)
Экземпляры: ДО (20180212) / Инвентарный номер: 62456 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 26 / ББК: 84(2Рос=Рус)6